Determinan Kemiskinan Pekerja Sektor Pariwisata di Provinsi Daerah Istimewa Yogyakarta Saat Pandemi COVID-19 - Nalom, Gian Ananta; Sumarni, Cucu (Seminar Nasional Official Statistics, 2023)
The COVID-19 pandemic has increased poverty in Indonesia and one of the most affected sectors is tourism. Yogyakarta Province as tourist destination, experienced a decline in tourism during the pandemic which led to an increase in poverty and the emergence the phenomenon of working poor tourism sector. The study aims to analyze determinants of the poverty of tourism sector workers in Yogyakarta Province during the pandemic. Data from Sakernas August and BPS publications 2020 with the binary logistic multilevel method. The results showed that during the pandemic, female; aged over 55 years; junior high school and below; working less than a year; working hours less than 35 hours a week; not using internet; and working in tourism services other than trade, transportation, and accommodation services had a greater chance of being working poor. In addition, tourist visits reduce the tendency of tourism sector workers to be woorking poor in Yogyakarta Province.